Urgensi Pelaksanaan Corporate Social Responsibility Pada Perusahaan Di Indonesia Perspektif Ekonomi Islam: Sebuah Meta-Sintesis - Ridwanto, Ridwanto; Misbach, Irwan; Siradjuddin, Siradjuddin (STIE AMKOP, 2023)
Corporate that is succeed in implementing CSR practices effectively can gain the public trust, improve the company’s image and reputation, and support the achievement of further development goals. In the context of Islamic Economics, CSR is not only considered as an additional social responsibility, but also as an obligation that must be in line with Islamic business ethics. Implementing CSR within an Islamic economic framework is an integral part of the company's commitment to providing a sustainable positive impact in society. This research uses a meta-synthesis method to investigate the implementation of CSR in companies in Indonesia from an Islamic economics perspective. Literature analysis shows that CSR provides certainty of welfare to employees, contributes to community empowerment, and ensures environmental sustainability. These findings provide depth insight into the importance of implementing CSR in achieving sustainable development goals and Islamic economic values in Indonesia.